Effect of carbon footprint on agricultural productivity in Nigeria: an empirical analysis (2024)
This study examines the relationship between carbon footprint (CFP) components and agricultural productivity in Nigeria, a critical area of investigation given the country's reliance on agriculture for economic stability, food security, and employment. Using time series data from 1990 to 2020, sourced from the Central Bank of Nigeria (CBN) and the World Bank, this study analyzes the effect of carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) emissions on agricultural output. Employing Robust Least Square (RLS) regression and the Error Correction Model (ECM), the study finds that CO2 and CH4 emissions negatively affect agricultural productivity, with 1% increases in CO2 and CH4 emissions leading to approximate decreases in agricultural output by 2% and 3%, respectively. Conversely, a 1% increase in N2O emissions correlates with an 8% increase in agricultural output, attributed to the use of nitrogen- based fertilizers. The results confirm the presence of long-run equilibrium relationships among the variables, with approximately 32% of the previous year's disequilibrium corrected annually. The study's findings align with the Environmental Kuznets Curve (EKC) hypothesis, suggesting that Nigeria is in the early stages of economic growth where environmental degradation is pronounced. These insights underscore the need for sustainable agricultural practices and effective carbon emission mitigation strategies to enhance food security and support economic growth in Nigeria.